Analisis Teks Yosua 1:8 Terhadap Memori Dan Aplikasinya Untuk Meningkatkan Prestasi Remaja Di Sekolah Menengah Pertama Glugur, Medan - Tulus, Jekson; Duha, Sang Putra Immanuel (Sekolah Tinggi Teologi Real Batam, 2024)
In this highly competitive era, characterized by rapid advancements in digital technology, adolescents familiar with technology are expected to be responsible and achieve excellence. Intellectual development plays a crucial role, which is achieved through the learning process. The awareness of the need to learn must be fostered through self-motivation, especially for adolescents with strong spirituality. Religious attitudes, particularly the frequency of prayer, Bible reading, and attending church services, are key factors shaping the spirituality of Christian youth. This study focuses on the influence of Bible reading on enhancing the intelligence of adolescents at SMP Sei Glugur Medan. Using an exegetical approach to Joshua 1:8 and memory psychology, the researcher aims to explore the role of memory in retaining God’s word. The findings show that meditating on the scriptures, rather than merely reading them, significantly enhances the spirituality and memory capacity of adolescents, leading to intellectual development. These findings are expected to enrich teaching methods. Keywords: exegesis; adolescent education; memory psychology; spirituality; religiosityAbstrakDi era yang sangat kompetitif dengan perkembangan teknologi digital yang pesat, remaja yang akrab dengan teknologi dituntut untuk bertanggung jawab dan meraih prestasi. Intelektual berperan penting dalam hal ini, yang didapatkan melalui proses belajar. Kesadaran untuk belajar perlu dibangun dengan motivasi diri, terutama bagi remaja yang memiliki spiritualitas tinggi. Sikap religius, khususnya frekuensi berdoa, membaca Alkitab, dan beribadah di gereja, menjadi faktor utama pembentuk spiritualitas remaja Kristen. Penelitian ini fokus pada pengaruh membaca Alkitab dalam meningkatkan kecerdasan remaja di SMP Sei Glugur Medan. Dengan pendekatan eksegesis teks Yosua 1:8 dan psikologi memori, peneliti ingin melihat peran memori dalam mengingat firman Tuhan. Hasil penelitian menunjukkan bahwa merenungkan firman, selain membacanya, meningkatkan spiritualitas remaja dan kemampuan memorinya, yang berdampak pada perkembangan intelektual. Diharapkan hasil ini membantu guru memperkaya metode pengajaran.Kata Kunci: eksegesis; pendidikan remaja; psikologi memori; spiritualitas; religiositas